Methodological Components for Evaluating Intervention Effectiveness of SOS Feeding Approach: A Feasibility Study - Schoen, Sarah A.; Balderrama, Rachel; Dopheide, Emma; Harris, Ariel; Hoffman, Laura; Sasse, Samantha (Children (Basel), 2025)
Background/Objectives: There is a paucity of research that explores the effectiveness of the Sequential Oral Sensory (SOS) Approach to Feeding. The purpose of this feasibility study was to evaluate the necessary components for the implementation of a treatment effectiveness study on the Sequential Oral Sensory (SOS) Approach to Feeding. The primary aims were to develop a fidelity measure, determine the feasibility of video coding, create an observational coding scheme, and determine if the outcome measures were sensitive to change. Methods: Over a 4-year period, data were collected from twelve participants aged 4 to 8 years with developmental disorders, with the assistance of four occupational therapy doctoral students. A fidelity measure was created, and inter-rater reliability was established among the four coders. Videotapes were collected at home and in the clinic. A behavioral coding system, consistent with the SOS Steps to Eating hierarchy, was developed for scoring feeding behaviors. Results: The preliminary inter-rater reliability was reported, and the coding results were represented graphically. Two additional outcome measures were piloted—a visual analog scale (VAS) and the Parenting Stress Index (PSI). The VAS was sensitive to changes in each parent’s ability to support their child, as well as in each client’s progress. The PSI also showed sensitivity to changes in the decline of parent-reported stress and child stress indices. Conclusions: Findings demonstrate fidelity to the SOS Approach, as well as sensitive outcomes, using behavioral coding and parent-reported measures. These evidence-based tools and procedures offer researchers and clinicians objective and meaningful feeding outcomes.